2009
DOI: 10.1111/j.1467-7687.2009.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of experience during childhood in shaping the other‐race effect

Abstract: It is well known that adults' face recognition is characterized by an 'other-race effect' (ORE; see Meissner & Brigham, 2001), but few studies have investigated this ORE during the development of the face processing system. Here we examined the role of experience with other-race faces during childhood by testing a group of 6- to 14-year-old Asian children adopted between 2 and 26 months in Caucasian families living in Western Europe, as well as a group of age-matched Caucasian children. The latter group showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 34 publications
12
95
1
Order By: Relevance
“…However, perceptual exposure to other-race faces does not necessarily lead to a reduction in the ORE. Caucasian adults who reported having extensive contact with African (Chiroro & Valentine, 1995) or Asian ( Ng & Lindsay, 1994) individuals nevertheless showed a robust ORE. Similarly, Korean children adopted between 2 and 26 months of age by Caucasian families and raised in a Caucasian environment do not show a reverse ORE for Asian faces (de Heering, de Liedekerke, Deboni & Rossion, 2010). In addition to perceptual experience, motivation to individuate people from the other-race seems to be an important factor for ameliorating the ORE (Levin, 2000), although the source of the ORE is still an open question.…”
Section: Holistic Processes and The Other-race Effectmentioning
confidence: 95%
“…However, perceptual exposure to other-race faces does not necessarily lead to a reduction in the ORE. Caucasian adults who reported having extensive contact with African (Chiroro & Valentine, 1995) or Asian ( Ng & Lindsay, 1994) individuals nevertheless showed a robust ORE. Similarly, Korean children adopted between 2 and 26 months of age by Caucasian families and raised in a Caucasian environment do not show a reverse ORE for Asian faces (de Heering, de Liedekerke, Deboni & Rossion, 2010). In addition to perceptual experience, motivation to individuate people from the other-race seems to be an important factor for ameliorating the ORE (Levin, 2000), although the source of the ORE is still an open question.…”
Section: Holistic Processes and The Other-race Effectmentioning
confidence: 95%
“…In terms of the neural responses measured in both groups at the N170 component, we found that while large-town observers had robust differences between face and non-face amplitudes (which is typical of N170 response properties), small-town observers exhibited a smaller amplitude difference between faces and chairs, which suggests poorer category selectivity at this particular component. These results suggest that like biased experience favoring own-race faces over other-race faces (de Heering et al 2010), the overall amount of face exposure observers receive during development affects their ability to recognize faces of all categories effectively.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, developmental studies have shown that the ORB is absent in very young children and only emerges during the first year of life [18], unless perceptual training with other-race faces during this critical stage prevents it ([19], for related findings, see [20]). Similarly, the ORB has been found to be absent [21] or even reversed [22] in Asian adults that were adopted and raised by European families, suggesting a strong influence of visual experience on our capacity to deal with faces from our own compared to other ethnicities.…”
Section: Introductionmentioning
confidence: 97%